2019
DOI: 10.1111/cid.12798
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiographic, and restorative peri‐implant measurements of narrow and standard diameter implants in obese and nonobese patients: A 3‐year retrospective follow‐up study

Abstract: Background: There is dearth of studies assessing clinical, restorative, and radiographic peri-implant outcomes around narrow diameter implants (NDIs) and standard diameter implants (SDIs) in obese and nonobese subjects.Objective: To assess clinical, restorative, and radiographic parameters of NDIs and SDIs placed in obese and nonobese individuals. Materials and Methods: Obese and nonobese patients requiring NDIs and SDIs in the anterior maxilla/mandible were included. Based on the implant diameter, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Although there is no consensus in the literature on the definition of narrow implants, in general, implants with a diameter narrower than 3.5 mm are considered narrow whereas implants with diameters narrower than 3.0 mm are described as extra-narrow or mini implants. 8 Reduced bleeding, postoperative discomfort, and healing time are some of the reported advantages of these implants when compared with grafting procedures. 4 Moreover, narrow and extranarrow implant survival rates from 80% to 100% were reported in a follow-up period of up to seven years.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no consensus in the literature on the definition of narrow implants, in general, implants with a diameter narrower than 3.5 mm are considered narrow whereas implants with diameters narrower than 3.0 mm are described as extra-narrow or mini implants. 8 Reduced bleeding, postoperative discomfort, and healing time are some of the reported advantages of these implants when compared with grafting procedures. 4 Moreover, narrow and extranarrow implant survival rates from 80% to 100% were reported in a follow-up period of up to seven years.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
“…A self-conducted literature search revealed a confusing variety of terms and dimensions for implants with reduced diameter. Implants with diameters between 1.8 and 2.4 mm [ 23 , 24 ], < 3.0 mm [ 5 ], or 3.0 mm [ 25 ] were designated by different authors as “mini-implants.” Several other authors labeled implants with diameters of 3.0 mm [ 26 ], 3.0 to 3.5 mm [ 5 , 27 ], < 3.3 mm [ 19 , 28 ], 3.3 mm [ 29 33 ], ≤ 3.5 mm [ 34 ], or < 5.0 mm [ 35 ] as “narrow implants.” Other common designations for MDI were “small implants” (3.0 to 3.5 mm) or “diameter reduced implants” (3.3 mm). Hence, a consensus for a clear cut-off point between implants with a standard diameter and implants with a reduced, non-standard diameter is still missing.…”
Section: Discussionmentioning
confidence: 99%